The role of risk, regret, and rejoice in non‐instrumental information seeking. (15th July 2022) - Mechera‐Ostrovsky, Tehilla; Liew, Shi Xian; Newell, Ben R.
Abstract: Standard theories suggest that humans should seek information only when it can help them make better decisions. However, recent work suggests that people choose to seek information even when it cannot influence the outcome of a choice. Across three experiments, we examined how this preference for non‐instrumental information was related to the risk, regret, and rejoice associated with different choices. Experiment 1 examined how risk preference informed the appetite for non‐instrumental information and tested how risk and information preference in a gamble‐task related to the desire for knowledge across a range of hypothetical real‐world scenarios. In Experiment 2, we tested how risk, operationalized as variance, related to non‐instrumental information seeking when allowing participants to mentally simulate the potential outcomes of gambles. In Experiment 3, we provided explicit feedback about forgone options, intending to make the potential for regret or rejoice more salient. Taken together, our results show a consistent appetite for information that was robust to changes across all experimental manipulations. We found some evidence of a positive correlation between the desire for knowledge and the level of anticipated regret (Experiment 1), but overall, our data appear more consistent with the idea that non‐instrumental information seeking is driven by a general aversion to uncertainty than by an attempt to regulate specific future emotions.